Hispolon Induces Apoptosis, Suppresses Migration and Invasion of Glioblastoma Cells and Inhibits GBM Xenograft Tumor Growth In Vivo - Kuan-Fu Liao; Tsung-Lang Chiu; Shu-Fang Chang; Mei-Jen Wang; Sheng-Chun Chiu (Molecules, 2021)
Hispolon, a polyphenol compound isolated from Phellinus linteus, has been reported to exhibit antioxidant, antiproliferative, and antitumor activities. This study aimed to explore the antitumor effects of hispolon on glioblastoma multiforme (GBM) cells in vitro and in vivo. The results revealed that hispolon significantly inhibited GBM cell proliferation and induced apoptosis through caspase-9 and caspase-3 activation and PARP cleavage. Hispolon also induced cell cycle G2/M phase arrest in GBM cells, as supported by flow cytometry analysis and confirmed by a decrease in cyclin B1, cdc2, and cdc25c protein expressions in a dose- and time-dependent manner. Furthermore, hispolon suppressed the migration and invasion of GBM cells by modulating epithelial–mesenchymal transition (EMT) markers via wound healing, transwell assays, and real-time PCR. Moreover, hispolon significantly reduced tumor growth in DBTRG xenograft mice and activated caspase-3 in hispolon-treated tumors. Thus, our findings revealed that hispolon is a potential candidate for the treatment of GBM.